Tree Species Are Differently Impacted by Cumulative Drought Stress and Present Higher Growth Synchrony in Dry Places - Gazol, Antonio; Camarero, J. Julio; Sangüesa-Barreda, Gabriel; Serra-Maluquer, Xavier; Sánchez-Salguero, Raúl; Coll, Lluís; Casals, Pere (Frontiers in Forests and Global Change, 2020)
The increase in frequency and intensity of droughts due to climate change might threaten forests under stress levels causing dieback and mortality episodes. Thus, deciphering how tree species from within a region respond to drought along environmental gradients should help us to understand forest vulnerability to climate change. To enlighten contrasting drought responses of dominant tree species, we reconstructed vegetation activity using Normalized Difference Vegetation Index (NDVI) and radial growth using tree-ring width series. We studied six tree species, three angiosperms (Fagus sylvatica, Quercus humilis, and Quercus ilex) and three gymnosperms (Pinus sylvestris, Pinus nigra, and Pinus halepensis), inhabiting a Mediterranean region in north-eastern Spain. We investigated if reduced growth resilience and increased growth synchrony after successive droughts (1986, 1989, 2005 and 2012): (i) were related to cumulative drought stress and (ii) preceded forest dieback in dry sites as compared to wet sites. In 2016, dieback affected Q. ilex and P. sylvestris stands in dry sites showing lower growth rates and NDVI. No dieback symptoms were observed in other species from dry (P. nigra, P. halepensis) or wet (F. sylvatica, Q. humilis, P. sylvestris) sites. Hot and dry summer conditions constrained growth and reduced NDVI. During 2005, a severe drought affected all species, but growth drops were more marked in dry places. All species were able to recover after extreme droughts, albeit angiosperms displayed lower than expected values of growth after the 2012 drought. Growth synchrony was higher in dry sites than in wet sites, and the differences were higher after the 2005 drought. This study reveals that the sensitivity of tree species to drought in species inhabiting the same region is species dependent, and it is contingent on local conditions with higher effects in dry sites than in wet sites. We describe how a cumulative impact of successive droughts increases growth synchrony and triggers the occurrence of dieback events in Mediterranean forests.